Changes in haptoglobin genotype-based gene expressions upon the observance of dawn-to-dusk intermittent fasting: a prospective cohort study on overweight and obese individuals - Madkour, Mohamed I.; Hassan, Rasha E.; Sherif, Naglaa M.; Awadallah, Samir; Farahat, Nada M.; Abdelrahim, Dana N.; AlHasan, Fatima A.; Taneera, Jalal; Faris, MoezAlIslam E. (Frontiers in Nutrition, 2024)
Introduction Intermittent fasting (IF) has been reported to be involved in ameliorating oxidative stress and lessening the systemic-low grade inflammation that predisposes to chronic diseases. Gene polymorphism is currently a main determining factor for the metabolic responses to different dietary and lifestyle modifications. Methods The current study was designed to explore the effect of observing four-week, dawn to dusk IF by participants with obesity on gene expression of the anti-inflammatory CD163, oxidative stress, and bioenergetics enzymes (SOD2, Nrf2, and TFAM), as well as metabolic and cellular regulatory genes (SIRT1 and SIRT3). Further, the study aimed to find out how haptoglobin (Hp) polymorphism modulates gene expression of the aforementioned genes and to determine changes in relative gene expressions of the aforementioned six genes based on Hp polymorphism in response to IF. Haptoglobin genotype was determined for the study subjects, and gene expressions were determined using qPCR. Gene expressions were assessed before and at the end of four consecutive weeks, dawn to sunset IF. Results The expressions of CD163, SOD, NfF2, and TFAM genes have significantly increased at the end of IF. At the same time, SIRT3 significantly decreased, implying that observing four consecutive weeks of dawn-to-dusk IF may enhance antioxidative stress response and reduce systemic inflammation. Conclusion Participants with genotypes Hp2-1 and Hp2-2 revealed upregulation of the antioxidant genes in response to the metabolic stress induced by IF compared with Hp1-1, implying that Hp polymorphism plays a key role in shaping the body’s response to dietary modifications such as fasting.